2016
DOI: 10.1590/0102-311x00049015
|View full text |Cite
|
Sign up to set email alerts
|

Incentives and barriers to HIV testing in men who have sex with men in a metropolitan area in Brazil

Abstract: Incentives and barriers to HIV testing in men who have sex with men in a metropolitan area in Brazil Incentivos e barreiras para testagem do HIV em homens que fazem sexo com homens em região metropolitana do Brasil Incentivos y barreras para el test del VIH en hombres que practican sexo con hombres en una región metropolitana de Brasil

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…This demand was likely driven by the privacy of e-testing, which systematic reviews have highlighted as a priority for MSM [23]. Similarly, the large number of HIVST packages delivered by mail, compared to packages retrieved in the public pharmacy, was likely related to introducing delivery models that addressed challenges such as travel distances, wait times at facilities, and confidentiality issues [45,46], all of which have been previously cited as barriers to testing.…”
Section: Discussionmentioning
confidence: 99%
“…This demand was likely driven by the privacy of e-testing, which systematic reviews have highlighted as a priority for MSM [23]. Similarly, the large number of HIVST packages delivered by mail, compared to packages retrieved in the public pharmacy, was likely related to introducing delivery models that addressed challenges such as travel distances, wait times at facilities, and confidentiality issues [45,46], all of which have been previously cited as barriers to testing.…”
Section: Discussionmentioning
confidence: 99%
“…In line with our findings, other studies indicated that MSM and transwomen preferred not to know their HIV status until they experienced illness ( Safren et al , 2006 ). Furthermore, studies have shown that predominant barriers to HIV testing include the fear of being diagnosed with HIV and fear of discrimination due to positive testing result ( Risher et al , 2013 ; Zhang et al , 2013 ; Goncalves et al , 2016 ). Therefore, it is crucial to formulate appropriate messages that address such barriers.…”
Section: Discussionmentioning
confidence: 99%
“…Another study carried out among MSM older than 18 years old in Fortaleza found that the majority were young (40.3%), unmarried (85.1%), had between 5 and 11 years of schooling (57.3%), and had a low income (37.6%), with 58.1% having been tested for HIV at some time in their lives, 34.1% have been tested to ensure that they were not infected, and 34% tested owing to the national campaign Be Aware 20 , which reinforces the need for this campaign. The reason for not taking the HIV test is to show trust the partner (21%) and the fear of discrimination if the test is positive (20.3%).…”
Section: Discussionmentioning
confidence: 99%
“…The reason for not taking the HIV test is to show trust the partner (21%) and the fear of discrimination if the test is positive (20.3%). Among MSM, the majority (97.6%) reported at least one advantage for the serological testing, and the remaining reported knowledge on serology testing (91.3%), immediate onset of treatment (83.5%), use of protection to avoid opportunistic diseases (56.7%), having sex without fear (55.6%), and increasing the quality of survival with HIV (54.1%) 20 . These vulnerabilities and fears served as barriers to the spontaneous performance of the exam, as also described by Terto Junior 21 .…”
Section: Discussionmentioning
confidence: 99%